The Role and Position of the Iraqi Communist Party in the March 11, 1970 Agreement - Mamkhool, Rafeeq R.; Hassaf, Prof.Dr. Esmael M. (Mitanni Journal of Humanitarian Sciences, 2023)
summary The Communist Party of Iraq (CPI) is one of the political and popular organizations that has played a prominent and influential role in the political arena of Iraq in general and Kurdistan in particular. In the September Revolution, especially in the political and military events between 1963-1970, they played a prominent and influential role in the events and developments. In this context, we will discuss the role and attitude of the Iraqi Communist Party towards the March 11, 1970 agreement, which is considered an important stage in the political history of Iraq and the Kurdish liberation movement. This research consists of an introduction, three topics, conclusions, a list of sources and a summary of the research in Arabic and English. Our research plan is divided into three themes: Topic 1 / Steps to start a conversation Topic 2: The role of the Iraqi Communist Party in the negotiations Topic 3 / Iraqi Communist Party and the March 11, 1970 Agreement